Estrogen inhibits hepatocellular carcinoma progression dependent on HOXA11-AS/HOXA11 - Pincheng Zhou; Fengze Sun; Peixu Lin; Yan Yan; Jiayao Liu; Yang Zhou; Ting He; Pengcheng Liu; Jie Wang; Huanhuan Sun; Haiqing Ma (Translational Oncology)
Background: The role of estrogen in liver cancer cells has attracted attention, but its specific actions and underlying mechanisms remain unclear. Methods: Flow CytoMetry and Western blotting were used to investigate the mechanism of HOXA11-AS and estrogen in promoting apoptosis of hepatocellular carcinoma (HCC). In vivo subcutaneous tumorigenesis assays were uesd to confirm the regulatory role of HOXA11-AS in HCC progression. Through immunohistochemistry, the correlation between HOXA11 expression and the prognosis of patients with HCC was explored. Results: Estrogen was found to promote apoptosis in HCC cells, dependent on HOXA11-AS. HOXA11 and HOXA11-AS are upregulated in HCC tissues. Downregulation of HOXA11-AS and HOXA11 significantly inhibited cell proliferation, migration, and invasion in HCC. HOXA11-AS forms an RNA duplex with HOXA11, preventing RNase degradation. In HCC patients, high HOXA11 expression was significantly associated with lower overall survival (OS) (p=0.001) and disease-free survival (DFS) (p=0.002). High HOXA11 expression was also significantly correlated with recurrence (p<0.001), major vascular invasion (p=0.002) and increased tumor volume (p=0.007). Estrogen activated the c-met/AKT/mTOR pathway in the HCC cell line. Conclusion: Estrogen and its related proteins have therapeutic effects in HCC and may be new potential therapeutic targets.